2018
DOI: 10.1017/s0031182018001105
|View full text |Cite
|
Sign up to set email alerts
|

A new landscape of host–protozoa interactions involving the extracellular vesicles world

Abstract: Extracellular vesicles (EVs) are released by a wide number of cells including blood cells, immune system cells, tumour cells, adult and embryonic stem cells. EVs are a heterogeneous group of vesicles (~30-1000 nm) including microvesicles and exosomes. The physiological release of EVs represents a normal state of the cell, raising a metabolic equilibrium between catabolic and anabolic processes. Moreover, when the cells are submitted to stress with different inducers or in pathological situations (malignancies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…Emerging data supports that BMSCs exert their positive effect by releasing EVs, which may be more effective. EVs, which are typically approximately 30-1000 nm in size and are composes of exosomes, microvesicles and apoptotic bodies, are membranous bodies that are released by almost all cells [28,29]. EVs attract more attention in the field of organ regeneration because they selectively packed with s proteins, mRNAs, microRNAs, and lipids [30].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data supports that BMSCs exert their positive effect by releasing EVs, which may be more effective. EVs, which are typically approximately 30-1000 nm in size and are composes of exosomes, microvesicles and apoptotic bodies, are membranous bodies that are released by almost all cells [28,29]. EVs attract more attention in the field of organ regeneration because they selectively packed with s proteins, mRNAs, microRNAs, and lipids [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that inflammatory responses occur during T. cruzi infection and that this can be reproduced by the parasite EVs (Nogueira et al, 2015). Likewise, Dr Ramirez's group showed that metacyclic-trypomastigotes induce the release of TGF-β coated plasma membrane vesicles from blood macrophages and lymphocytes, which could further increase parasite infectivity (Cestari et al, 2012;Wyllie and Ramirez, 2017;Gavinho et al, 2018;Rossi et al, 2019). However, it is unknown whether EVs released by T. cruzi-infected macrophages or EVs isolated from parasite modulate hotst inflammatory responses and cell invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, simultaneous secretion of exosomes and plasma membrane blebs has been predicted among Leishamania spp (Montaner et al, 2014 ). The biogenesis and classification of exosomes and other EVs have been expertly reviewed in depth by Garcia-Silva et al ( 2014 ), Colombo et al ( 2014 ), and Gavinho et al ( 2018 ). The internal volume of an exosome ranges between 20 and 90 nm 3 with a capacity to lodge an estimated 100 proteins and 10,000 nucleotides, values that should be higher in ectosomes and apoptotic bodies (Torró et al, 2018 ).…”
Section: Ppevs: Formation Characterization and Subcellular Originmentioning
confidence: 99%
“…EVs also play important roles as channels of intercellular communication within parasite population (Gavinho et al, 2018 ). Additionally, as suggested by Geiger et al ( 2010 ), T. brucei may possibly use MVs to communicate between trypanosomes by exchanging non-protein cytosolic receptors or genomic information to harness survival strategies.…”
Section: Functions Of Ppevsmentioning
confidence: 99%